Hybrid Areas of Work Between Employment and Self-Employment: Emerging Challenges and Future Research Directions - Murgia, Annalisa; Bozzon, Rossella; Digennaro, Pierluigi; Mezihorak, Petr; Mondon-Navazo, Mathilde; Borghi, Paolo (Frontiers in Sociology, 2020)
The growth of non-standard employment relations has created one of the major challenges in terms of workers’ rights as well as collective representation in European societies. Among non-standard employment relations, the so-called ‘solo self-employed’ – self-employed workers without employees – are challenging the very foundations of our labour markets, that is to say the opposition between employers and employees, fostering the development of emerging ‘hybrid’ areas of work. The heterogeneity of the solo self-employed is difficult to capture from official statistics, which are still based on traditional classifications, and questions also the legal categories that qualify these workers. Moreover, the fact that solo self-employed workers do not form a homogenous group, and are diverse in terms of their activities, interests and needs, calls for changes in the way trade unions, employer organisations, and new freelancer associations develop collective actions, claims-making activities and strategies of organising. With the aim to achieve an in-depth understanding of the increasingly extensive and populated categories of the solo self-employed, this contribution aims at reconstructing the state of the art within different fields of study, such as employment relations, labour law, industrial relations and social movements, and at offering some possible future research directions.